INTRODUCTION: POST-GADDAFI REPERCUSSIONS IN THE SAHEL AND WEST AFRICA (The Strategic Review for Southern Africa, 2020)
The areas south of Libya have experienced more than their fair share of conflict and rapid social change. In earlier times, the main routes of trade, commerce and pilgrimage between West African and the Arab Peninsula passed through this region, also once inhabited by mighty warrior empires (see for example Bawuro 1972). However, as the empires along these routes faded away, and international ocean shipping opened up this part of Africa to the forces of global trade and capitalism, the centres of authority that once controlled this region also vanished. What remained was an almost open territory: unwelcoming and hard, but also a place of possibilities and the freedom to roam for those who had mastered the art of survival under such difficult conditions. This was the land of the Tuareg and other semi-nomadic groups who controlled cities and important trading posts such as Timbuktu, Gao and Kidal in contemporary Mali. This is the world of the Sahel and the parts of Western Africa that straddles Libya, and a region that currently includes Southern Algeria, Northern Mali, Niger, Chad, Mauritania and parts of Northern Nigeria. These are therefore also the countries and areas that have come to experience the full effect of what we define as post-Gaddafi repercussions.